RP-HPLC analysis for the simultaneous estimation of rabeprazole sodium and aceclofenac in a combined dosage form - Khokra, Sukhbir Lal; Choudhary, Balram; Mehta, Heena (International Current Pharmaceutical Journal, 2012)
A rapid, simple and highly sensitive reversed phase high performance liquid chromatographic (RP-HPLC) method has been developed for the quantitative determination of Rabeprazole sodium and Aceclofenac in a combined dosage form. Rabeprazole sodium and Aceclofenac were chromatographed using C-18 column as stationary phase and methanol: acetonitrile: water (60 : 10 : 30 v/v/v) as the mobile phase at a flow rate of 1.0 ml/min at ambient temperature and detected at 280 nm. The retention time (RT) of Rabeprazole sodium and Aceclofenac were found to be 5.611 min and 2.102 minute, respectively. The linearities of Rabeprazole sodium and Aceclofenac were in the range of 1-10 µg/ml and 3-15 µg/ml, respectively. The limit of detection was found to be 0.091 µg/ml for Rabeprazole sodium and 0.043 µg/ml for Aceclofenac. The proposed method was applied for the determination of Rabeprazole sodium and Aceclofenac in a combined dosage form and result was found satisfactory. DOI: http://dx.doi.org/10.3329/icpj.v1i12.12450 International Current Pharmaceutical Journal 2012, 1(12): 410-413